2017
DOI: 10.1038/s41598-017-11982-8
|View full text |Cite
|
Sign up to set email alerts
|

Balance between hydration enthalpy and entropy is important for ice binding surfaces in Antifreeze Proteins

Abstract: Antifreeze Proteins (AFPs) inhibit the growth of an ice crystal by binding to it. The detailed binding mechanism is, however, still not fully understood. We investigated three AFPs using Molecular Dynamics simulations in combination with Grid Inhomogeneous Solvation Theory, exploring their hydration thermodynamics. The observed enthalpic and entropic differences between the ice-binding sites and the inactive surface reveal key properties essential for proteins in order to bind ice: While entropic contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…For a more detailed discussion of the theoretical background, we recommend the studies described in [40,50,51]. For a better glimpse of the state of the art concerning the recent usability of this technique in different and complex biochemical systems, accurate examples can be found in [50,52,53].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more detailed discussion of the theoretical background, we recommend the studies described in [40,50,51]. For a better glimpse of the state of the art concerning the recent usability of this technique in different and complex biochemical systems, accurate examples can be found in [50,52,53].…”
Section: Methodsmentioning
confidence: 99%
“…These subsites, in turn, are computationally described as different voxels v. This per voxel ΔG sol value (here called ΔG v sol ), in turn, can be naturally split in two respective enthalpic and two respective entropic per voxel terms as shown in (4):ΔG v solv= ΔE vsw+ ΔE v ww TΔSvtrans TΔSvorient where the enthalpic terms Δ sw and ΔE ww are the respective solute–water and water–water interaction energies per voxel, as calculated by the molecular mechanics’ force field. The solvation entropy terms, in turn, encompass the respective contributions of the translational ΔS trans and orientational (i.e., angular) Δ S orient of the water molecules around the different voxels, defined as Shannon entropies and algorithmically calculated via the nearest neighbor estimats and orientational (i.e., angular) Δ S orient of the water molecules around the different voxels, defined as Shannon entropies and algorithmically calculated via the nearest neighbor estimation [42,52,53,54]. All terms depicted in (4) are state functions, and therefore, need a reference state.…”
Section: Methodsmentioning
confidence: 99%
“…17 Even though this mechanism is now widely accepted, molecular details of each step have yet to be fully understood. 18,19 Because of its overall amphiphilic character and hydrophobic IBS, AFP III is also likely to have a relatively high affinity for hydrophobic interfaces. For instance, it has been shown that even at very low concentrations, AFP III reduces water's surface tension, indicating its strong propensity to be localized at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, grid inhomogeneous solvation theory (GIST) allows the analysis and thermodynamic quantification of the solute–solvent interaction on a grid over the whole trajectory [ 42 , 43 ]. Prior studies have shown that GIST can be used to identify favorable interaction sites in heterocycles [ 44 , 45 ] or in biomolecules, [ 43 , 46 , 47 ] for example, in antifreeze proteins [ 47 ] and kinases [ 46 ]. In the latter studies, the grid points were further analyzed to identify positions with high water density to visualize locations of strongly interacting solvent molecules.…”
Section: Introductionmentioning
confidence: 99%